2007
DOI: 10.1124/jpet.107.124859
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Kallikrein Is Involved in the Cardioprotective Effect of AT1-Receptor Blockade in Acute Myocardial Ischemia

Abstract: Angiotensin-converting enzyme inhibitors limit infarct size in animal models of myocardial ischemia reperfusion injury. This effect has been shown to be due to inhibition of bradykinin degradation rather than inhibition of angiotensin II formation. The purpose of this study was to determine whether angiotensin AT1 receptor blockade by losartan or its active metabolite EXP3174 protects against myocardial ischemia-reperfusion injury in mice and whether this protection is mediated by the kallikrein kinin system. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
36
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 39 publications
6
36
0
Order By: Relevance
“…12 Our finding that icatibant prevented the cardioprotective effect of aliskiren is consistent with the involvement of B 2 receptors, although unlike other studies we did not detect an effect of icatibant on valsartan-induced cardioprotection. 25,[27][28][29] Many previous studies have shown interaction between the B 2 and AT 2 receptors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…12 Our finding that icatibant prevented the cardioprotective effect of aliskiren is consistent with the involvement of B 2 receptors, although unlike other studies we did not detect an effect of icatibant on valsartan-induced cardioprotection. 25,[27][28][29] Many previous studies have shown interaction between the B 2 and AT 2 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…12 Our finding that icatibant prevented the cardioprotective effect of aliskiren is consistent with the involvement of B 2 receptors, although unlike other studies we did not detect an effect of icatibant on valsartan-induced cardioprotection. 25,[27][28][29] Many previous studies have shown interaction between the B 2 and AT 2 receptors. [33][34][35][36][37][38] Siragy et al 35 showed that PD123319 suppressed basal bradykinin levels and prevented valsartan-induced increase in bradykinin levels in renal interstitial fluid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They also found that chronic AT1 blockade is associated with reduced myocardial apoptosis in essential hypertension [15] . The beneficial effects of angiotensin-converting enzyme inhibition in hypertension, cardiovascular and renal disease can be partially attributed to kinin accumulation resulting from the activation of the B2 receptor [16,17] . Previous animal studies suggested that kallikrein/kinin protects against myocardial apoptosis after ischemia/reperfusion injury [18,19] .…”
Section: Discussionmentioning
confidence: 99%